The Influence of Social Symptoms in Society on Legal Development - Mukhidin (LEGAL BRIEF, 2021)
Social changes that have been and are still going on have resulted in a new formulation and thinking about law and its relation to society. The interaction between law and society is a result of a law being passed. In society, they will not be separated from the social symptoms that will befall them. The existing social changes are a symptom that comes from the passing of the law. The interaction of law and society is a reciprocal effort between law and society, both individuals and groups. In the sociology of law it can be stated that all behavior that arises as a result of the existence of the law being enforced is the result of or the result of the application of the law in society. Social symptoms can arise due to deviations from the prevailing norms in society.